Economic resilience and the role of fiscal policy in the Asean-5 countries - Muhammad Zakir, Abdullah (2019)
ASEAN–5 countries are vulnerable to external shocks as these countries are highly integrated with external markets through international trade and foreign capital flow. These countries have experienced huge negative economic impact during the Asian Financial Crisis (AFC) and the Global Financial Crisis (GFC). The aim of this study is to evaluate the economic resilience in the ASEAN–5 countries, to examine the role of fiscal policy as a shock – absorber and, to determine the effectiveness of fiscal policy in stabilizing the economy during the AFC and the GFC. The Ordinary Least Square (OLS) with robust standard error and Autoregressive Distributed Lag (ARDL) analyses are used in the estimation using time series data for the period of 1981 – 2014. The result reveals that Thailand has the highest shock amplification impact among the countries. For shock persistent dimension, Singapore is the highest among the countries. The finding also indicates that automatic stabilizer plays a shock absorber role for all countries. For discretionary fiscal tool, the result shows that it could play a role as a shock absorber in Malaysia, Singapore and Thailand but not for Indonesia and the Philippines. Furthermore, the result reveals that the impact of automatic stabilizers on the economy was effective during the AFC for all countries except for the Philippines. Discretionary fiscal tool is found to be effective for Singapore and Thailand but ineffective for Malaysia, Indonesia and the Philippines during the AFC. During the GFC, automatic stabilizers are effective for all countries except for Thailand. In contrast, discretionary fiscal tool is found to be ineffective for all countries. In the context of policy implication, the study recommends strengthening trade and financial integration among ASEAN members which could reduce external vulnerability and increases economic resilience.